Review of the New World genus Cholomyia (Diptera, Tachinidae), with a new species from Costa Rica - Santis,Marcelo Domingos de (2016)
ABSTRACT The tachinid genus Cholomyia presents Neotropical and Nearctic distribution with three species: C. acromion (Wiedemann, 1824), C. filipes (Walker, 1857), and C. inaequipes Bigot, 1884. In the present paper, all species are reviewed and redescribed, and a new species from Costa Rica is described, C. zumbadoi sp. nov. An identification key based on males is provided. For the first time, the male terminalia of all species, and the female terminalia and first instar larva of C. inaequipes are described and illustrated. Finally, based on the detailed morphological study we discuss the systematic placement of Cholomyia into Myiophasiini-Tachininae. A list of host–parasite records is synthesized.